AMPK/SIRT1 Deficiency Drives Adjuvant-Induced Arthritis in Rats by Promoting Glycolysis-Mediated Monocytes Inflammatory Polarization - Wang DD; He CY; Wu YJ; Xu L; Shi C; Olatunji OJ; Zuo J; Ji CL (Journal of Inflammation Research, 2022)
Dan-Dan Wang,1,2,* Chi-Yi He,3,* Yi-Jin Wu,1,2 Liang Xu,4 Chao Shi,1 Opeyemi Joshua Olatunji,5 Jian Zuo,1,6,7 Cong-Lan Ji8 1Xin’an Medicine Research Center, The First Affiliated Hospital of Wannan Medical College (Yijishan Hospital), Wuhu, 241000, People’s Republic of China; 2The Key Laboratory of Anti-Inflammatory and Immune Medicine, Ministry of Education, Institute of Clinical Pharmacology, Anhui Medical University, Hefei, 230032, People’s Republic of China; 3Department of Gastroenterology, The First Affiliated Hospital of Wannan Medical College (Yijishan Hospital), Wuhu, 241000, People’s Republic of China; 4Department of Rheumatology, The First Affiliated Hospital of Wannan Medical College (Yijishan Hospital), Wuhu, 241000, People’s Republic of China; 5Traditional Thai Medical Research and Innovation Center, Faculty of Traditional Thai Medicine, Prince of Songkla University, Hat Yai, 90110, Thailand; 6Key Laboratory of Non-coding RNA Transformation Research of Anhui Higher Education Institution, Wannan Medical College, Wuhu, 241000, People’s Republic of China; 7Anhui Provincial Engineering Laboratory for Screening and Re-evaluation of Active Compounds of Herbal Medicines in Southern Anhui, Wuhu, 241000, People’s Republic of China; 8School of Pharmacy, Anhui College of Traditional Chinese Medicine, Wuhu, 241000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Cong-Lan Ji; Jian Zuo, Email 37709103@qq.com; zuojian8178@163.comBackground: Exact roles of many metabolic regulators in rheumatoid arthritis (RA) are to be clarified. This study aimed to further characterize the impacts of silent information regulator 1 (SIRT1) status changes on this disease.Methods: Fluctuation pattern of SIRT1 expression in adjuvant-induced arthritis (AIA) rats was monitored using periodically collected white blood cells. Another bath of AIA rats were treated by SIRT1 agonist resveratrol. Blood from these rats was used to separate monocytes and plasma, which were subjected to polymerase chain reaction (PCR), enzyme linked immunosorbent assay (ELISA), and biochemical analyses. Clinical implication of SIRT1 activation was verified by treating AIA rat monocytes with SIRT1 agonist and overexpression vector in vitro.Results: SIRT1 deficiency occurred in AIA rats, which was accompanied with down-regulation of interleukin 10 (IL-10) and arginase-1 (ARG-1). Resveratrol eased oxidative stress and increased IL-10 production in vivo. Results of ELISA analysis demonstrated that resveratrol attenuated AIA severity in rats. Furthermore, it restored the altered levels of triglyceride, lactate and pyruvate in blood. Resveratrol promoted IL-10 production, and suppressed glycolysis of AIA monocytes cultured in vitro. SIRT1 overexpression similarly reshaped differentiation profile of AIA monocytes, evidenced by changes in metabolism indicators, IL-10 production and AMP-activated protein kinase (AMPK) pathway status. Although overexpressing SIRT1 in normal cells did not affect glycolysis significantly, it attenuated AMPK antagonist-caused abnormality.Conclusion: SIRT1 deficiency is implicated in AIA-related immune abnormality and metabolism alteration. Activating this signaling with resveratrol would impair the inflammatory polarization of monocytes, and consequently ease the severity of RA.Keywords: inflammation, metabolic reprogramming, monocytes, resveratrol, rheumatoid arthritis